Advances in Mechanisms of Portal Vein Thrombosis in Liver Cirrhosis - WU Yarong; ZHANG Yongqiang; ZHENG Ying; WANG Caihong (Xiehe Yixue Zazhi)
Portal vein thrombosis (PVT) is one of the most common complications of liver cirrhosis. The formation of PVT can increase the mortality rate of cirrhotic patients and adversely affect the successful implementation and prognosis of liver transplantation. A hypercoagulable state is a unique mechanism underlying PVT formation in cirrhotic patients. In recent years, the pathogenesis of PVT has gradually been elucidated, with specific mechanisms including the following aspects: systemic and local inflammatory responses lead to vascular endothelial cell dysfunction, thereby promoting the activation of the coagulation system; abnormal activation of the monocyte-macrophage system exacerbates local inflammation, enhancing platelet adhesion and aggregation, and facilitating thrombus formation; an imbalance between the coagulation and fibrinolytic systems results in a sustained hypercoagulable state; and intestinal microbiota dysbiosis induces inflammation and metabolic disturbances, thereby increasing the risk of PVT. This article summarizes the latest research progress on these key mechanisms and their interactions, providing new insights into the molecular and cellular mechanisms of PVT. It also offers directions for the early diagnosis of PVT and the exploration of novel intervention strategies in the future.